Gesunde Menschen machen: Die deutsch-deutsche Geschichte der Gesundheitsaufklärung, 1945–1967 - Sammer, Christian (Ordnungssysteme, 2020)
Christian Sammer draws upon the East German Hygienics Museum and the West German Health Museum to examine media-based and institutional continuities along with efforts to restart health education between 1945 and 1967. He shows how the intersections between medical expertise, advertising concepts, and conceptions of social order formed the ideal “responsible citizen” and “socialist personality.”